PENGARUH EDUKASI KETERAMPILAN BASIC LIFE SUPPORT MENGGUNAKAN VIDEO TERHADAP TINGKAT PENGETAHUAN DAN KETERAMPILAN MAHASISWA KEPERAWATAN MUHAMMADIYAH GORONTALO - Haslinda Damansyah; Pipin Yunus (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Basic Life Support (BLS) or in Indonesian known as Basic Life Assistance is an effort made to maintain life when the patient or victim experiences a life-threatening condition. Objective: to determine the influence of Basic Life Support of skills education on Knowledge level and Skills of Nursing Students. Method: The design of this research was Quasi Experiment with the One Group pre-post Test Design. The sample in this research were 61 respondents with collecting by used purposive sampling technique. Results: Based on the statistical tests it has a significant value of 0,000 (p <0.05). Therefore Ho is rejected, meaning that there is a significant influence before and after given education used video. Conclusion: there is the effect of basic life support skills education used video on the knowledge level and skills of nursing students in Muhammadiyah university of Gorontalo.